Ethnodemography of Bashkirs in Regions of Russia (1970—2010) - F. G. Safin (Tsentr nauchnykh i obrazovatelnykh proektov, 2021)
The issues of ethno-demographic and ethno-linguistic development of the Bashkir population in the regions of the Russian Federation are considered. It is noted that the tendencies of demographic processes among the Bashkirs in the regions and in the republic of the same name are very different. The features of the ethnodemographic development of the Bashkirs in the regions of their historical settlement are shown, in which general trends coincide with the demographic processes in the country as a whole. It cannot be said about the Republic of Bashkortostan, which is characterized by sharp fluctuations in the size of the titular ethnic group. The dynamics of the ethnic and linguistic identity of the Bashkir population in the regions of historical settlement is revealed in a comparative aspect with the subjects to which the Bashkirs moved at a later time and in which their number is a small proportion. The novelty of the study lies in the fact that it was the first to analyze the ethno-demographic and ethno-linguistic aspects of the development of the Bashkirs in the Russian Federation, including in the regions of their historical settlement. The relevance of the study is due to the fact that the issue of the demographic development of the Bashkir population at the present stage, especially in the republic of the same name, has acquired an ethnopolitical discourse. It has been proven that, despite the policy of reviving ethnicity and the native language, the Bashkirs, like other peoples, are gradually losing it in favor of being recognized as a native Russian.